2020
DOI: 10.21873/anticanres.14018
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Adjuvant Aromatase Inhibitor Therapy Among Postmenopausal Hispanic/Latino Women With Breast Cancer

Abstract: The mean age was 61.6±9.4 years, and 109 (91.6%) selfidentified as Hispanic/Latino. A total of 58% reported an annual income of $15,000 or less. Overall, 40.3% had completed eighth grade or less education, 31.9% high school, and 12% had obtained a technical degree. The majority of patients (56%) had either a medium (45%) or a low level of adherence (11%). High adherence was noted in 44% of participants. Seven (5.6%) patients scored 2 or below on a 4-point scale for intentional adherence, and 18 (13.5%) scored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Considering that antihormonal aromatase must be taken daily and that forgetfulness is one of the barriers to medication adherence among breast cancer survivors, 18–20 interventions involving daily reminders would be more beneficial than those based on weekly reminders. In this study, the duration of reminder intervention was 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that antihormonal aromatase must be taken daily and that forgetfulness is one of the barriers to medication adherence among breast cancer survivors, 18–20 interventions involving daily reminders would be more beneficial than those based on weekly reminders. In this study, the duration of reminder intervention was 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard method to measure medication adherence precisely (25) . Non-adherence is a multifactorial problem that affects therapy outcomes and lead to disease recurrence, re-hospitalization, and decrease survival rate (26) . Several studies found that socioeconomic status and clinical data including older age, single, low income and out-of-pocket cost of AHT (26)(27)(28)(29)(30)(31) , comorbidity, treatment side effects, depression (32)(33)(34) are associated with non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…These portals can also support patient communication with providers about managing their symptoms [38]. This strategy reduced anxiety and improved treatment adherence among patients undergoing active treatment with endocrine therapy or oral chemotherapy [2,3]. This adherence is important because hormone therapy reduces deaths due to breast cancer; yet, almost 50% of patients do not complete standard 5-year courses of treatment [39,40].…”
Section: Adherencementioning
confidence: 99%
“…In fact, Black women are 40% more likely than White women to die of breast cancer due to genetic predisposition, aggressive tumor biology, differential access to health care, and social determinants of health [2]. Compared with White women, racial and ethnic minority groups, as well as rural and underserved populations, have less access to specialty care for breast cancer and a disproportionate risk of breast cancer-specific mortality associated with poverty, obesity, and lower treatment adherence [2][3][4].…”
Section: Introductionmentioning
confidence: 99%